Correlation study of drug abuse knowledge and infectious disease prevention in adolescent health policy - Dwi Nur Siti Marchamah; Revalina Alya Syaharani; Wahyuni Arumsari (Universitas Jenderal Achmad Yani Yogyakarta, 2026)
Background: Drug abuse and the increasing risk of infectious diseases among adolescents are interrelated health issues that require serious attention.Objective: This study aims to analyze the relationship between knowledge about drug abuse and infectious disease prevention efforts among adolescents.Methods: The study used a quantitative analytical approach with a cross-sectional design and was conducted from February to April 2026 at Junior High School X Semarang. The study sample consisted of 188 respondents selected using a cluster random sampling technique. Data were collected through a Google Form-based questionnaire that had been tested for validity and reliability. Results: The study showed that the majority of respondents had a high level of knowledge (96.8%) and a high level of infectious disease prevention efforts (95.7%). However, statistical tests showed no significant relationship between the two variables (p-value = 0.126).Conclusion: These findings indicate that knowledge alone is not sufficient to influence preventive behavior, necessitating a more comprehensive approach to adolescent health interventions.